Manajemen Pelayanan Publik: Lampiran UU No.25 Tahun 2009 Tentang Pelayanan Publik - NURMANDI, Achmad (Sinergi Publishing, 2010)
Manajemen Pelayanan Publik: Lampiran UU No.25 Tahun 2009 Tentang Pelayanan Publik